2006
DOI: 10.1002/mats.200500062
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology and Dynamics of Substrate Effects on Spinodal Decomposition in Binary Mixtures with Short‐Range Potential

Abstract: Summary: The SDSD of binary mixture with short‐range potential is numerically simulated in 3D by cell dynamic system (CDSs), focusing on the phase morphology and dynamics in the parallel cross‐sections. The formation mechanism and growth law of the wetting layer are analyzed taking thermal noise effects into account. The simulated results show that the phase inversion in the parallel cross‐sections can be observed near the substrate interface. Without thermal noise, the growth law of the wetting layer is simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…They found that the surface enrichment layer grew logarithmically where there was no noise term, while it followed the LS growth law when noise was present. [37] The effect of critical quench depth on the wetting layer growth rate showed three different regimes: the pure diffusion-limited growth law for shallow quench (exponent 1/2), a logarithmic growth for intermediate quench, and the LS growth law for deepest quench were observed. [38] The results of off-critical quenches illustrated when the minority component was attracted to the surface, the growth of the wetting layer versus quench depth followed three different regimes similar to the critical quench case.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…They found that the surface enrichment layer grew logarithmically where there was no noise term, while it followed the LS growth law when noise was present. [37] The effect of critical quench depth on the wetting layer growth rate showed three different regimes: the pure diffusion-limited growth law for shallow quench (exponent 1/2), a logarithmic growth for intermediate quench, and the LS growth law for deepest quench were observed. [38] The results of off-critical quenches illustrated when the minority component was attracted to the surface, the growth of the wetting layer versus quench depth followed three different regimes similar to the critical quench case.…”
Section: Introductionmentioning
confidence: 97%
“…[27][28][29] Therefore, a wide range of studies on SDSD has been carried out. [13][14][15][16][17]26,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] Jones et al [40] were the first to experimentally study the SDSD of a binary polymer mixture. They investigated phase separation of perdeuterated poly(ethylenepropylene) (d-PEP) and poly(ethylenepropylene) (PEP) as an isotopic polymer mixture under temperature quenches to T = 35 C and 76 C, at the presence of a surface preferably attracting d-PEP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface-directed phase separation (SDPS) mechanism has attracted much attention and has been studied intensively for the past two decades as a means of fabricating binary materials with unique phase separated morphologies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Surfaces have a great impact on the structure and associated properties of multiphase polymeric materials, including polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that to model the SDPS and to be capable of replicating experimental observations, only one length scale should be used. Yan and Xie [15,16] simulated the SDPS in a polymer system by the cell dynamic system method. For the case of short range potential, they found that the wetting layer grows according to the logarithmic growth law if the noise term is absent, while it will grow according to the Lifshitz-Slyozov 1/3 growth law if the noise term is present.…”
Section: Introductionmentioning
confidence: 99%